Analisis Hubungan dan Pengaruh Variabel â€œMarketing Mix 7Pâ€ terhadap Keputusan Memilih Perguruan Tinggi Swasta di Tangerang Raya - Paulus Yulius Fanggidae (Akmenika: Jurnal Akuntansi dan Manajemen, 2023)
The challenges of today's higher education institutions, apart from the rapid environmental changes on one side and the other, are that universities must provide various facilities and infrastructure as well as attractive programs to support the process of "delivery" of educational services to their learning citizens so that they can provide the best service. in the â€œservice encounterâ€ for this of course this activity requires the executors to be careful in making the right policies and marketing programs so as to attract prospective students and to be able to register as students. Related to this, in this study the researcher analyzed the primary data which was collected using a questionnaire with the sample being all high school students in the Greater Tangerang Region and processed using statistical methods using SPSS, calculating using numerical methods and to see the relationship and the effect using multiple linear regression method where the Variable "Market-ing Mix 7P" (Product, Price, Place, Promotion, People, Process and Physical Evidence) as an independent variable which turns out to have a significant and positive influence on the Decision to Choose Private Higher Education Â